TRAINING and DEVELOPING a FINANCIAL REPORT APPLICATION for BUMG in COT MENTIWAN VILLAGE, ACEH BESAR REGENCY - Syawalina, Cut Fitrika; Fatma, Surya; Susanti, Eva; Suryani, Irma; Salsabila, Salsabila (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Villages are the spearhead of Indonesia's development. Therefore, the government continues to strive to boost the village economy through the distribution of Village Funds and the development of the Village-Owned Enterprises (BUMDes) program. The objectives of BUMDes as stated in Permendesa PDT and Transmigration No. 4/2015 are to improve the village economy, improve community efforts in managing village economic potential. Village funds can be used to establish village-owned enterprises to boost the village economy. The phenomenon of managing Village-Owned Enterprises (BUMG) also occurred in Cot Mentiwan Village, where it turned out that there were still several obstacles faced by village officials in managing BUMG Desa. So far, the bookkeeping carried out by BUMG managers has only been in the form of records of incoming and outgoing cash expenditures. Based on this phenomenon, through this community service activity, the focus is to help village officials by providing education to BUMDes managers in preparing BUMG financial reports using digital financial applications through the SIAPDes Application.Keywords : Digital Marketing, E-Commerce, Digital Business Applications